Aplikasi Pembelajaran Interaktif Buku Tematik Subtema Manusia dan Lingkungan untuk Siswa Kelas V : Interactive Learning Application for Thematic Book Subtheme Human and Environtment for Fifth Grade Students - Fieny Eunike Rorong; Virginia Tulenan; Meita Rumbayan (Universitas Sam Ratulangi, 2023)
In facing the demands of the modern world. The use of technology in education has become a way for students to quicly adapt to the changes of the times. If students are solely focused on reading books, often this can pose challenges in therms of engagement and understanding in the leaning process. Therefore, an interactive learning application is created to enhance the understanding of fifth-grade students at SD GMIM Sea regarding the Thematik Subtheme of “Human and Environment” within the Thematic Book. This application is Android-based and constructed using the Multimedia Development Life Cycle (MDLC) software development method. The results of the research conducted among 30 fifth-grade students at SD GMIM Sea show that there is a 38% increase in correct answers from an average pre-test score of 31% before using the application, and there is a 69% increase in post-test scores after using the application. The questionnaire results indicate that 90% of students responded that this application can enhance their understanding of human and environmental subjects. Thus, this study produces an interactive learning application that can enhance the understanding of fifth-grade students at SD GMIM Sea regarding the Thematic Subtheme of “Human and Environment” within the Thematic Book.